Representation of tamils in post war sinhala movies: special reference to movies produced during 2010- 2012 - Sivapriya, S. (University of Jaffna, 2016)
An exciting aspect of inter cultural communication is the communication processes through which one culture's perceptions of another culture are created and recreated. From a Symbolic Interactions perspective, the perceptions one culture has of another are constructed through interaction with and about the target culture. Media messages are primary sources of messages that shape one culture's perceptions of another. The existing literature insists that dominant culture often try to maintain their role as powerful and superiors among the subordinate cultures. This study uses content analysis of Sinhala movies to explore the ways in which Tamils are represented in the post war Sinhala movies and to analyze how those images contribute to the development of cultural perceptions about Tamils in Sri Lanka. The quantitative data collected through content analysis were further analyzed using qualitative approaches. The results indicate that Tamils are portrayed as cruel soldiers who are very strong about their mission and even kill their own corps for their mission, minority characters who depend on Sinhalese for their survival, depended who could be rescued by the army, emotionally weak and violent. Overall, the findings prove that Sri Lankan Sinhala war movies produced during the post war period develop a negative perception about Tamils in Sri Lanka.
Keywords: : Inter- cultural communication; Symbolic interactionism; Sinhala movies